1987
DOI: 10.3382/ps.0660055
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Feeding Mature White Leghorn Hens Diets that Contain Deoxynivalenol (Vomitoxin)

Abstract: Mature White Leghorn hens that had been fed a commercial laying diet were changed to a wheat-based diet over a period of 42 days. Two groups were formed based on equivalent egg production and body weights and randomly assigned to either a control (noncontaminated) wheat diet or a naturally contaminated deoxynivalenol (DON, vomitoxin) wheat diet (18 mg DON/kg). Hens were provided their respective diets and water ad libitum for 112 days along with 16 hr of light. The DON-contaminated diet did not significantly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 8 publications
3
6
0
Order By: Relevance
“…Feeding DON-contaminated wheat did not significantly affect fertility, hatchability of fertile eggs, hatch of total eggs set, or chick weights at hatch. These data agree with the results of Hamilton et al (1985a), Moran et al (1983), and Kubena et al (1987).…”
Section: Resultssupporting
confidence: 95%
See 4 more Smart Citations
“…Feeding DON-contaminated wheat did not significantly affect fertility, hatchability of fertile eggs, hatch of total eggs set, or chick weights at hatch. These data agree with the results of Hamilton et al (1985a), Moran et al (1983), and Kubena et al (1987).…”
Section: Resultssupporting
confidence: 95%
“…In the present study, significant differences in body weights due to dietary treatment, were not observed at any of the time intervals between 24 and 48 wk of age. These results agree with Hamilton et al (1985a), Moran et al (1983), and Kubena et al (1987) who also found no significant differences in body weights at these ages.…”
Section: Resultssupporting
confidence: 95%
See 3 more Smart Citations